The Parallax Memory. Notes on the Solidarity, Solidarity… Collection - Klejsa, Konrad (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
The Parallax Memory. Notes on the Solidarity, Solidarity… Collection The paper focuses on Solidarity, Solidarity…, a collective project made in 2005 to celebrate the 25th anniversary of the worker’s movement. Thirteen novelettas demonstrate various approaches towards the so-called “Polish August” of 1980, ranging from “comemorational”, praising the leaders of the movement, to critical, stimulating new interpretations of Polish history. The theoretical foundation of the analysis is built upon Deleuze’s theory of “time-image”. Although it may be argued that Deleuze’s work deals primarily with film style and the historically shifting aesthetics of the cinema, it is also justifiable to state that (if treated metaphorically) the Deleuzean “Time-Image” is based on the concept of a journey into the realms of the Forgotten, whereas its spectator is forced to rework his position in the field of history. In the paper, special attention is given to episodes which deal with the nature of history in a specific way. In Jacek Bromski’s short story, a former dissident asks his oppressor for a loan, leading to a replay of his interrogation. In Robert Glinski’s short story, Japanese tourists take pictures of the deserted Gdynia shipyard where Solidarity began. In Juliusz Machulski’s novelette, Solidarity never happened, so the director ponders making a movie about the heroic Battle of Lenino. These short films trace the inability to cope with the heritage of Solidarity, which became a deserted space in public debate during the course of its demolition and reconstruction.